Proposed new interior design for Sate Kajang Haji Samuri Restaurant at Lot 3 & 4, Waterfront Bistro, Esplanade Wing Lumut Waterfront, 32020, Lumut, Perak Darul Ridzuan / Fiq’ha Nur Amira Shahfuzi - Shahfuzi, Fiq’ha Nur Amira (Faculty of Architecture, Planning and Surveying, 2010)
The titled of my project study is Proposed New Interior Design for Sate Kajang Haji Samuri Restaurant at Lot 3 & 4, Waterfront Bistro, Esplanade Wing Lumut Waterfront, 32020 Lumut, Perak Darul Ridzuan. It is located near the beach. It is a good spot to build up a new restaurant because there is no sate restaurant around there.The target market of this traditional food is mostly people whoever wish to eat sate. The first branch restaurant from the product at Kajang, Selangor is one of the way for the company to expand their target market and business. The main objective of this project is to portray a new look for the product and the restaurant. There are a few of methodology and techniques have been used to achieve this objective. There are three phase for each methodology. It depends on how cooperative the client and how we strive for the information to be included in this report.The restaurant needs a new concept and images that shows the looks of a sense of delight. It is key important to give a better images for this restaurant referring back to the main objective of this proposal yet to improvise the products marketing strategies.